Juventudes quilombolas : cotidianos e modos de vidas na comunidade Morrinho/MT - Santos, Zizele Ferreira dos (2022)
This study seeks to reflect on the Ways of Life of Quilombola youths. In this sense, an inventory was drawn up based on research proposals of a socio-qualitative nature in order to observe the daily lives of young people from the rural Black Community Quilombo Morrinho, in the municipality of Poconé-MT. Young people were taken as social subjects in the expectation of reflecting on the fabrics, plots and daily representations, composing a look at the “unsaid”, but explicit, in the relationships between these individuals and the community in the preparations for the “Festas de Santo” between 2019 and 2020. Thus, the research was anchored from the methodological perspective of the Sociology of Daily Life, from which the following steps were constituted: a) systematic literature review (RSL) as a method; b) field work, through data collection using resources such as: photography, recordings, informal conversations; field notes from participant observation and the organization of the various aspects of the research, namely: the social group and the central objective of the study, translated into the questioning “how the ways of life of quilombola youths are constituted, concerning the manifestations of Africanity Brazilian?". We identify the ethos of these youth cultures, key elements for the constitution of their unity as a Being integrated into the composition of the world, in harmony with everything around us. These Ways of Life point to the possibility of making efforts to implement Quilombola School Education based on proposals for pluriversal education, attentive to the ways of educating present in quilombola communities, spaces that show themselves as formators of life content.